Assessment of person-centeredness in healthcare and social support services for women with unintended pregnancy (CarePreg): protocol for a mixed-method study - Isabelle Scholl; Martin Härter; Pola Hahlweg; Jördis M Zill; Anja Lindig; Lara Maria Reck (BMJ Open, 2022)
Introduction For women with unintended pregnancy, access to high-quality care has been found limited due to social stigma and legal restrictions, especially when seeking abortion. To foster person-centeredness (PC), recognising the experiences and needs of women is the first premise. This study aims to (1) identify relevant dimensions of PC (2) evaluate PC in healthcare and social support services, (3) develop recommendations for further actions in healthcare and social support services for women with unintended pregnancy.Methods and analysis We will use a mixed-methods approach. Phase 1: expert workshops with 10–15 healthcare professionals and counsellors and semistructured interviews with 15–20 women with unintended pregnancy will be conducted to assess the relevance of PC dimensions. Phase 2: quantitative assessment of PC dimensions within healthcare and support services will be conducted. We aim to include 600 women with an unintended pregnancy (1) until 24 weeks of pregnancy or (2) who sought abortion within the past 8 weeks, over three measurement points within 12 months. To deepen the results, semistructured interviews will be conducted. Phase 3: a workshop with 10–15 experts and an online survey with 100–150 experts will be used to indicate recommendations. Participants will be gained through relevant care facilities. An ethical advisory board and an advisory board of affected women will be involved throughout the study.Ethics and dissemination The study will be carried out in accordance to the latest version of the Helsinki Declaration of the World Medical Association and principles of good scientific practice. The study was approved by the Local Psychological Ethics Committee of the University Medical Center Hamburg-Eppendorf, Germany (LPEK-0260). Written informed consent will be sought prior to study participation. The study results will be disseminated in scientific journals, through collaboration partners and plain language press releases.